A Systematic Literature Review on the Perceptions of Teachers of STEM Integration - Guerzon, John Michael; Busbus, Stephenie (SEAMEO QITEP in Science, 2023)
Low academic performance of students has always been a challenge in science and mathematics education despite the introduction of different constructivist approaches, like STEM integration, to promote student learning. The beliefs and perceptions of teachers about a certain approach were believed to shape curriculum implementation. This necessitates a review of the perceptions of teachers of STEM integration. PRISMA 27-item components of reporting systematic literature review were employed to extract patterns relevant to the benefits, challenges, and recommendations identified by K-12 teachers. From n=721, only five research articles were left for final review after a four-phase screening process. Teachers generally view STEM integration as promoting student achievement (problem-solving skills) and motivation or interest. There is an emerging view that science integration in mathematics instruction is stronger than mathematics integration in science instruction. Interestingly, a misperception was identified about technology education integration. This implies incorporation of STEM integration concepts in the undergraduate curriculum as teacher preparation was identified as one of the main problems on which improvements may be focused. The lack of equipment to support technology education integration as well as the appropriate skills needed to deliver the lesson was another emerging theme. In turn, the need for upskilling programmes to support the teachers in delivering 21st-century learning approaches is emphasised. Content knowledge is a prerequisite to pedagogical knowledge. To implement STEM integration, teachers need to know the contents of the different disciplines integrated.